From Partnership Policy to Sustainability Outcomes: How FPKMS Shapes the Multidimensional Sustainability of Oil Palm Smallholders - Ahmad Wadud; Diana Chalil; Surya Abadi Sembiring (Universitas Pattimura, 2026)
The Facilitation Program for Surrounding Community Plantation Development (FPKMS), introduced under Indonesia's Ministry of Agriculture Regulation No. 18 of 2021, marks a policy shift from land-based partnership schemes toward farmer empowerment and institutional strengthening. Despite its strategic importance, evidence explaining how FPKMS translates partnership implementation into sustainability outcomes remains limited. This study evaluates FPKMS implementation and examines its influence on the multidimensional sustainability of oil palm smallholders. A comparative survey was conducted among 120 smallholders, comprising 60 FPKMS participants and 60 non-participants, in Langkat Regency, North Sumatra, Indonesia. Program implementation was assessed using the Input–Process–Output framework, while sustainability was measured through the Rap-PalmOil approach based on Multidimensional Scaling across ecological, economic, social, technological, and institutional dimensions. Model robustness was verified through stress statistics, coefficients of determination, Monte Carlo simulation, bootstrap confidence intervals, and Wilcoxon rank-sum tests. Partnered smallholders achieved a substantially higher multidimensional sustainability index than non-partnered farmers (79.5 vs. 27.2). Although program inputs remained limited, effective implementation processes and outputs strengthened social capital, institutional capacity, farmer participation, and organizational performance, thereby improving sustainability outcomes. These findings demonstrate that institutional empowerment, rather than direct financial support, constitutes the principal pathway through which partnership policies foster sustainable oil palm smallholder development. Strengthening program inputs and technological support is therefore essential for sustaining long-term ecological, economic, and technological performance.